A brief review of intradialytic hypotension with a focus on survival. Issue 6 (29th June 2017) - Chou, Jason A.; Kalantar‐Zadeh, Kamyar; Mathew, Anna T.
Abstract: Intradialytic hypotension (IDH), a common complication of ultrafiltration during hemodialysis therapy, is associated with high mortality and morbidity. IDH, defined as a nadir systolic blood pressure of less than 90 mm Hg on more than 30% of treatments, is a relevant definition and is correlated with mortality. Risk factors for IDH include patient demographics, anti‐hypertensive medication use, larger interdialytic weight gain, and dialysis prescription features as dialysate sodium, high ultrafiltration rate, and dialysate temperature. A high frequency of IDH events carries a substantial death risk. An ultrafiltration rate >10 mL/h/kg, and even more so >13 mL/h/kg, is highly predictive of cardiovascular and all‐cause mortality. Evidence suggests that IDH causes acute reversible segmental myocardial hypoperfusion and contractile dysfunction (myocardial stunning), which can result in long‐term loss of myocardial contractility, leading to premature death. IDH also has negative end‐organ effects on the brain and gut, contributing to mortality through stroke, and endotoxin translocation with associated inflammation and protein‐energy wasting. Given strong association of IDH and dialysis mortality, a paradigm shift to its approach is urgently needed. Randomized controlled trials are required to prospectively test drugs and monitoring devices which may reduce IDH.